Budaya Dayak dan Unsur-Unsur Magis dalam Novel Kembang Gunung Purei Karya Lan Fang - Cahyaningrum Dewojati; Ine Wulandari (JENTERA: Jurnal Kajian Sastra, 2022)
This study analyzes the dialectics and negotiation process between elements contained in the narrative mode of magical realism by Wendy B. Faris. The material object is Kembang Gunung Purei novel by Lang Fang. The novel raises the issue of friction between two different cultures. The character of Nanang is described as a modern and logical cultural agent of a big city, while Bua is described as a figure who comes from the traditional Dayak community who believes in local cultural customs and magical things to solve various problems in life. This cultural background difference causes the emergence of dialectical and negotiation processes which can be explained by the five elements of Wendy B. Faris’ magical realism, such as irreducible elements, phenomenal world, unsettling doubts, disruptions of time, space, and identity. The five elements seek to equate the dominant subject with the marginalized subject. The results of the study show that the dialectic and negotiation process paved the way for the possibility of heterogeneity, not only from the dominant discourse (Nanang-modern), but also the marginalized discourse (Bua-traditional), not only from the subject called ‘West’ (immigrants-foreigners-city), but also the subject of the so-called ‘Timur’ (Dayak tribe). AbstrakPenelitian ini membahas dialektika dan proses negoisiasi antarelemen yang terdapat dalam mode naratif realisme magis yang digagas oleh Wendy B. Faris. Objek material yang digunakan adalah novel Kembang Gunung Purei karya Lang Fang. Novel tersebut mengangkat isu gesekan antara dua budaya berbeda. Tokoh Nanang digambarkan sebagai agen budaya kota besar yang modern dan logis, sementara Bua digambarkan sebagai tokoh yang berasal dari masyarakat tradisional Dayak yang banyak meyakini adat budaya lokal dan hal-hal magis sebagai solusi berbagai masalah dalam kehidupan. Latar belakang budaya yang berbeda itulah penyebab munculnya proses dialektika dan negosiasi yang dapat dijelaskan dengan lima elemen realime magis Wendy B. Faris, seperti irreducible element, phenomenal world, unsettling doubts, disruptions of time, space, dan identity. Kelima elemen tersebut berupaya untuk menyetarakan subjek yang dominan dengan subjek yang termaginalkan. Hasil penelitian menunjukkan bahwa proses dialektika dan negosiasi membuka jalan bagi kemungkinan heterogenitas tidak hanya dari wacana yang dominan (Nanang-modern), melainkan juga wacana yang termaginalkan (Bua-tradisional), tidak hanya dari subjek yang disebut ‘Barat’ (pendatang-orang asing-kota), melainkan juga subjek yang disebut ‘Timur’ (suku Dayak).